Method of Extracting Speech Characteristics of Bugis Regional Language - Hartono, Sriwijanaka Yudi; Suyuti, Saidah (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2025)
his research focuses on developing an application to extract speech signal characteristics of Bugis regional speakers using Matlab and Wavesurfer software. The study centers on feature extraction, specifically Short Time Energy (STE), Autocorrelation Cepstral for pitch extraction, and Cepstrum Linear Predictive Coding (LPC) for formant analysis. Results indicate that male voices have greater signal energy than female voices. The pitch values for male speakers range from 52.29 Hz to 135.76 Hz, while female speakers' pitch ranges from 73.39 Hz to 242.42 Hz. The formant analysis showed that male and female speakers have distinct formant frequencies, with male speakers having lower formant frequencies. For instance, the first formant (f1) in male speakers ranges from 433.0 Hz to 590.3 Hz, while in female speakers it ranges from 273.9 Hz to 452.8 Hz. The pitch of male voices is concentrated between 50 Hz and 250 Hz, whereas female voices fall between 120 Hz and 500 Hz. Additionally, differences in formants (f1 to f5) were observed in the word